1996
DOI: 10.1016/0735-1097(95)00595-1
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous amiodarone in treatment of recent-onset atrial fibrillation: Results of a randomized, controlled study

Abstract: Intravenous amiodarone, at the doses used in this study, produces a modest but not significant benefit in converting acute atrial fibrillation to sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
3
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(128 citation statements)
references
References 16 publications
8
104
3
11
Order By: Relevance
“…[11][12][13][14] These discrepancies, perhaps, may occur by chance, as the study groups were small. The differences in patients' baseline characteristics, duration of index AF episode, and mode of 332 Table I.…”
Section: Conversion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] These discrepancies, perhaps, may occur by chance, as the study groups were small. The differences in patients' baseline characteristics, duration of index AF episode, and mode of 332 Table I.…”
Section: Conversion Ratementioning
confidence: 99%
“…The results of these studies are discordant: the efficacy rate varies from only 59% to as much as 92%. The remaining published studies [11][12][13][14][15][16] dealt either with patients with longer AF duration or oral loading of amiodarone.…”
Section: Conversion Ratementioning
confidence: 99%
“…64 Control of ventricular rate in AF was evaluated in 2 placebocontrolled studies, both of which reported significantly lower ventricular rates with amiodarone. 69,70 Thus, amiodarone is effective for acute conversion of AF and has a beneficial effect on heart rate in AF.…”
Section: Amiodarone For Afmentioning
confidence: 99%
“…55 Conversion to normal sinus rhythm may occur with amiodarone. Therefore, in patients at risk for systemic emboli, amiodarone is recommended only when other medications for rate control have proved ineffective or are contraindicated and the risk of possible pharmacological cardioversion is felt to be justified.…”
Section: Atrial Fibrillation/fluttermentioning
confidence: 99%
“…Therefore, in patients at risk for systemic emboli, amiodarone is recommended only when other medications for rate control have proved ineffective or are contraindicated and the risk of possible pharmacological cardioversion is felt to be justified. Some studies have found that whereas amiodarone was effective for rate control, conversion to sinus rhythm was no greater with conventional doses of IV amiodarone than placebo or digitalis, [55][56][57][58][59][60][61][62][63][64][65][66][67]160 particularly in refractory AF and clinical shock. Because of this concern amiodarone should be reserved for use within the first 48 hours of arrhythmia onset 62,78 or in patients in whom other rate-control measures are ineffective or contraindicated.…”
Section: Atrial Fibrillation/fluttermentioning
confidence: 99%